Analisis Metode Vise Kriterijumska Optimizajica I Kompromisno Resenje (VIKOR) dalam Merekomendasikan Pupuk Terbaik bagi Produktivitas Tanaman Kelapa Sawit - Nila Soraya Damanik; Eka Irawan; Muhammad Ridwan Lubis; Agus Perdana Windarto; Dedi Suhendro (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The purpose of this study was to analyze and apply decision support system software in recommending the best fertilizer for oil palm productivity. Sources of data were obtained from PTPN IV Marihat through observations and interviews with PTPN IV Marihat regarding the data used. The solution given is a ranking using the Vise Kriterijumska Optimizajica I Kompromisno Resenje (VIKOR) method. In selecting the best fertilizer for oil palm plant productivity, several parameters of the assessment criteria are used, including soil type (C1), nutrient content (C2), dosage (C3), shape (C4), properties (C5), and price (C6). The alternatives used as a composition in selecting the best fertilizer for oil palm plant productivity are Urea Fertilizer, SP-36 Fertilizer, KCL Fertilizer, Dolomite Fertilizer, and Abu Janjang Fertilizer. The results of research conducted with the VIKOR method that ranking can be applied to selecting the best fertilizer for oil palm plant productivity where the best alternative with the smallest Q value is Dolomite Fertilizer with a value of Q = 0, the second alternative is Urea Fertilizer with a value of Q = 0.626, the third alternative is KCL fertilizer with a value of Q = 0.678, the fourth alternative is Ash Janjang Fertilizer with a value of Q = 0.833, and the last alternative is SP-36 Fertilizer with a value of Q = 1. It is hoped that the results of this research can help PTPN IV Marihat in recommend the best fertilizer so that it can increasing oil palm productivity at PTPN IV Marihat.